Pengaruh Kualitas Pelayanan Karyawan terhadap Kepuasan Pelanggan di Salon Kecantikan Beautylicious Kota Padang - Nurul Khairani Aulia; Rahmi Oktarina (STIKes Ibnu Sina Ajibarang, 2024)
This study explores the effect of the influence of employee service quality on customer satisfaction at the beautylicious beauty salon in Padang city. In the era of globalisation, the beauty business is growing rapidly as people's needs for appearance increase, including treatments for men and women. Beauty salons such as Beautylicious in Padang have capitalised on this trend by providing beauty and body care services, but service quality still needs to be improved to meet customer expectations and maintain competitiveness in a competitive market. The purpose of this study is to analyse the effect of service quality provided by employees on customer satisfaction at Beautylicious Beauty Salon in Padang City. The method used in this research is a survey with 145 respondents who were analysed using SPSS and Smart PLS statistical software. This study measures the assessment of service quality and customer satisfaction, and calculates the relationship coefficient and significance value. The results showed that service quality obtained an average rating of 49.52 with a standard deviation of 16.375, indicating variations in customer expectations. In addition, the average rating for customer satisfaction was 50.84 with a standard deviation of 17.065. Regression analysis with Smart PLS resulted in an R-square value of 0.753, indicating that service quality contributed 75.3% to customer satisfaction.